Recent rapid changes in the spatio‐temporal distribution of West Nile Neuro‐invasive Disease in Italy. (14th October 2019) - Moirano, Giovenale; Richiardi, Lorenzo; Calzolari, Mattia; Merletti, Franco; Maule, Milena
Abstract: In Italy, the first human case of West Nile Virus (WNV) infection was reported in 2008 and, since then, the number of cases has been steadily increasing. In this study, we describe the temporal and spatial pattern of WNV infection risk among humans in Italy, focusing on the human cases of West Nile Neuro‐invasive Disease (WNND) observed between 2008 and 2017. Incidence rates are estimated for each year and province under study. The incidence temporal trend is estimated using Poisson regression, and a spatio‐temporal cluster detection analysis is performed to detect high‐risk areas. In total, 231 WNND cases were notified in Italy between 2008 and 2017. The annual incidence rates increased during the study period (annual percentage change: 11.7%; 95%CI: −0.9%; 26.1%). A geographical spread of the disease was observed during the study period throughout Northern Italy, with an increasing number of affected provinces. Provinces close to the Po River (the main river in the north of Italy) and the Oristano province (in the Sardinia Island) experienced the highest incidence rates during the study period. Our study shows a gradual, but rapid spread of WNND across Northern Italy from east to west and suggests the hypothesis that provinces close to Po River might present ecological and climatic conditions favourable to the virus circulation.